STRATEGI SEKOLAH MENENGAH KEJURUAN SWASTA BINA INFORMATIKA TANGERANG SELATAN MENANGANI KRISIS AGAR BERTAHAN SELAMA PANDEMI COVID-19 - Wibisono, Ramadhan; Syarif, Karmila (Jurnal Pendidikan Teknik dan Vokasional, 2022)
To avoid the transmission of covid-19 through physical or face-to-face meetings, the government had implemented policies ranging from Large-Scale Social Restrictions (PSBB) to the Implementation of Community Activity Restrictions (PPKM) Level 1 to Level 4. Private Vocational High Schools (SMKS) Bina Informatika South Tangerang, including private educational institutions affected by the implementation of PSBB and PPKM. Most educational activities are implemented online through the Zoom Meeting application or Google Meet. The new student acceptance rate (PPDB) decreased by 10% during the two years of the covid-19 pandemic because many parents lost their income and chose to send their children to public schools so that costs were cheaper. In addition, almost half of the students from several classes were delayed in paying their monthly school fees because their parents' income was decreasing. Not to mention that online learning is considered less effective due to several obstacles. Through this research, the author wants to know the strategy of SMKS Bina Informatika in dealing with the crisis to survive during the covid-19 pandemic. This study uses a qualitative method with a descriptive approach and SWOT analysis through library support to strengthen the results of the study. While the data collection techniques are through interviews, observation, documentation and triangulation or a combination. Based on the results of the study, when covid-19 cases increased at the beginning of the April 2020 pandemic, SMKS Bina Informatika implemented full online learning. Meanwhile, when the covid-19 pandemic slowed from August 2021 to March 2022, Bina Informatics implemented hybrid or 50% face-to-face learning. 100% face-to-face learning since April 2022 when the South Tangerang area was declared covid-19 free. To facilitate access to subject matter, student and teacher attendance, and assessment, the BI-SMART application is used which can be accessed via mobile phones and computers. For students whose parents are financially constrained, SMKS Bina Informatika provides a flexible payment deadline, and all students receive a 50% discount. For new students there is dispensation for tuition fees or school buildings can be repaid three to four times.